Review of Research Methods in the Study of L2 Writing Processes - Mamadiyeva , Gulbakhor; Nurmukhamedov, Ulugbek (Journal of Academic Writing, 2024)
While there are a number of books that address how to research first language (L1) and second language (L2) writing, there are not many accessible research manuals that guide novice researchers on how to research cognitive processes associated with L1/L2 writing. Researching L1/L2 writing processes and development requires a consideration of a number of variables because writing typically occurs in many different contexts (e.g., in-class, at home), settings (e.g., ESL vs. EFL), modalities (e.g., paper and pen, digital), and conditions (e.g., individual, collaborative). We find the edited volume Research Methods in the Study of L2 Writing Processes by Rosa Manchón and Julio Rocaa (2023) to be insightful for two reasons. First, all the chapters in the volume provide step-by-step directions in researching L1/L2 writing processes, highlight methodological concerns, and offer ideas on addressing those concerns. Second, the volume provides an excellent overview of key considerations in employing diverse research instruments to study writing processes.